2010
DOI: 10.1161/strokeaha.110.583229
|View full text |Cite
|
Sign up to set email alerts
|

Gait in Elderly With Cerebral Small Vessel Disease

Abstract: Background and Purpose-Gait disorders are common in the elderly and are related to loss of functional independence and death. White matter lesions (WMLs) may be related, but only a minority of individuals with WMLs has gait disorders. Probably other factors are involved, including location and the independent effect of frequently coinciding lacunar infarcts, the other aspect of cerebral small vessel disease. The aim of our study was to investigate the effect of both the severity and location of both WMLs and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 26 publications
12
109
2
Order By: Relevance
“…Subclinical infarcts, also called silent infarcts, are more clinically significant than the name would imply, as they can have effects on functional and clinical outcomes. 3,4,6,24 In exploratory analyses in the subsample for whom we could calculate the HOMA index, we found that leisure time physical activity is associated with fewer silent infarcts even after adjusting for insulin resistance. Engaging in physical activity may be an important strategy to reduce the prevalence of SBI and thus, potentially, improve functional outcomes.…”
Section: Mrimentioning
confidence: 84%
“…Subclinical infarcts, also called silent infarcts, are more clinically significant than the name would imply, as they can have effects on functional and clinical outcomes. 3,4,6,24 In exploratory analyses in the subsample for whom we could calculate the HOMA index, we found that leisure time physical activity is associated with fewer silent infarcts even after adjusting for insulin resistance. Engaging in physical activity may be an important strategy to reduce the prevalence of SBI and thus, potentially, improve functional outcomes.…”
Section: Mrimentioning
confidence: 84%
“…Murray et al (2004) found that functional decline was specifically associated with the presence of gait disorders and bradykinesia, but not with other MPS such as rigidity or tremor. Similarly, neuroimaging studies reveal that white matter lesions in the frontal and parietal lobes were linked to bradykinesia (de Laat et al 2012) and gait disturbances (de Laat et al 2010), suggesting a shared pathway between bradykinesia and gait in aging.…”
Section: Introductionmentioning
confidence: 97%
“…The primary gait outcomes were gait velocity and stride length, which correlate with disease severity in these patients [74]. The primary balance outcome was recovery of stance in the retropulsion test, with postural instability being a feature of small vessel disease and a common cause of falls in these patients [75].…”
Section: The Use Of Tdcs In Patients With Small Vessel Disease With Gmentioning
confidence: 99%
“…This may represent a large placebo effect in a patient who may not have felt confident to walk to his maximum capability before the stimulation. Alternatively, the effect size may reflect the nature of the subcortical stroke-gait function in patients with subcortical white matter disease can be more variable [74], perhaps relating to fluctuating attentional drive directed towards walking.…”
Section: The Use Of Tdcs In Patients With Gait Disturbance Following mentioning
confidence: 99%